Economic Costs and Adaptations for Alternative Regulations of California's Sacramento–San Joaquin Delta - Stacy K. Tanaka; Christina R. Connell-Buck; Kaveh Madani; Josue Medellin-Azuara; Jay R. Lund; Ellen Hanak (San Francisco Estuary and Watershed Science, 2011)
Stacy K. Tanaka, Christina R. Connell–Buck, Kaveh Madani, Josue Medellín-Azuara, Jay R. Lund, and Ellen Hanak doi: http://dx.doi.org/10.15447/sfews.2014v9iss2art4 Water exports from California’s Sacramento–San Joaquin Delta are an environmental concern because they reduce net outflows of fresh water from the Delta, and can entrain fish and disrupt flows within the Delta. If exports were no longer pumped from within the Delta, the regulatory issue becomes one of maintaining appropriate flows into and out of the Delta. This paper presents the results of two sets of hydro-economic optimization modeling runs, which were developed to represent a range of modified Delta operations and their economic and operational effects on California’s water supply system. The first set of runs represents decreasing export capacity from the Delta. The second set increases minimum net Delta outflow (MNDO) requirements. The hydro-economic model seeks the least–cost statewide water management scheme for water supply, including a wide range of resources and water management options. Results show that reducing exports or increasing MNDO requirements increase annual average statewide water scarcity, scarcity costs, and operating costs (from greater use of desalination, wastewater recycling, water treatment, and pumping). Effects of reduced exports are especially concentrated in agricultural communities in the southern Central Valley because of their loss of access to overall water supply exports and their ability to transfer remaining water to southern California. Increased outflow requirements increase water scarcity and associated costs throughout California. For an equivalent amount of average Delta outflows, statewide costs increase more rapidly when exports alone are reduced than when minimum outflow requirements are increased and effects are more widely distributed statewide.